Comparison of two different dosages of hydroxyzine for sedation in the paediatric dental patient - MAHMOUD FAYTROUNY, ZEYNEP OKTE, & ZUHAL KUCUKYAVUZ (IAPD and Blackwell, 2007)
Fearful children are one of the major problems in paediatric dentistry. When behaviour management techniques are insufficient, it is unavoidable to use a safe and inexpensive technique such as sedation.